Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Thus, the solutions of the quadratic equation x 2 + 5x + 6 = 0 are x = -2 and x = -3.
Answer:
See Below.
Explanation:
Quadratic Form:
[tex]a {x}^{2} + bx + c[/tex]
Quadratic Formula:
[tex]x = \frac{ - b + - \sqrt{ {b}^{2} - 4ac} }{2a} [/tex]
Based on the information given from the question, we can deduce:
a = 1
b = 6
c = -5
Now we can substitute all these values into the formula to find x.
[tex]x = \frac{ - 6 + - \sqrt{ {6}^{2} - 4(1)( - 5)} }{2(1)} \\ = - 3 + \sqrt{14} \: or \: - 3 - \sqrt{14} [/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.